2011
DOI: 10.1371/journal.pone.0023718
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endoglin Concentration Is Not Elevated in Chronic Kidney Disease

Abstract: BackgroundSoluble endoglin, a TGF-β receptor, plays a key role in cardiovascular physiology. Whether circulating concentrations of soluble endoglin are elevated in CKD or underlie the high risk of cardiovascular death associated with chronic kidney disease (CKD) is unknown.MethodsIndividuals with and without CKD were recruited at a single center. Estimated glomerular filtration rate (eGFR) was estimated using the modified MDRD study equation and the serum creatinine at the time of recruitment, and patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
1
Order By: Relevance
“…Doghish AS et al found that plasma soluble endoglin increased with the development of diabetic nephropathy with microalbuminuria 27) . However, Charytan DM analyzed soluble endoglin concentrations in a large cohort of individuals, with and without chronic kidney disease, and found no association between soluble endoglin levels and eGFR or urinary albumin excretion 38) .Our study showed soluble endoglin was inversely correlated with eGFR, but the association was not significant after further adjustment. The result indicates the former association may be produced by Quantitative variables are presented as means±standard deviation, quanlitative variables are presented as numbers with percentages.…”
Section: Resultscontrasting
confidence: 60%
“…Doghish AS et al found that plasma soluble endoglin increased with the development of diabetic nephropathy with microalbuminuria 27) . However, Charytan DM analyzed soluble endoglin concentrations in a large cohort of individuals, with and without chronic kidney disease, and found no association between soluble endoglin levels and eGFR or urinary albumin excretion 38) .Our study showed soluble endoglin was inversely correlated with eGFR, but the association was not significant after further adjustment. The result indicates the former association may be produced by Quantitative variables are presented as means±standard deviation, quanlitative variables are presented as numbers with percentages.…”
Section: Resultscontrasting
confidence: 60%
“…These data suggest that a substantial part of endoglin in fibrotic liver tissues is cleaved and subsequently released into the circulation system. This might be organ-specific, since, in kidney fibrosis (chronic kidney disease and end stage kidney disease), no changes in sol-eng were observed [123]. Although sol-eng was not elevated in patients, in mouse models for kidney fibrosis, unilateral ureteral obstruction (UUO) significantly elevated the mRNA expression of endoglin within the kidney.…”
Section: Endoglin-expressing Fibroblasts In Fibrosismentioning
confidence: 99%
“…They could not determine significant associations between serum endoglin levels and GFR or urine microalbumin levels. [ 25 ] We also could not identify a significant association between serum endoglin levels and GFR. However, our results revealed higher serum endoglin levels in patients with cSFK.…”
Section: Discussionmentioning
confidence: 69%